2011
DOI: 10.2522/ptj.20100368
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in Chronic Pelvic Pain in Women: Relevance and Application of the Fear-Avoidance Model of Pain

Abstract: Chronic pelvic pain in women is a debilitating, costly condition often treated by physical therapists. The etiology of this condition is multifactorial and poorly understood, given the complex interplay of muscles, bones, and soft tissue that comprise the pelvis. There are few guidelines directing treatment interventions for this condition. In the last decade, several investigators have highlighted the role of psychological variables in conditions such as vulvodynia and painful bladder syndrome. Pain-related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 79 publications
2
71
0
2
Order By: Relevance
“…CPP patients have eight times more psychosomatic symptoms than controls 7 . The presence of family issues in most CPP patients suggests the importance of using psychotherapy to treat these females, as already emphasized by the literature 8,18 . Further qualitative studies may probably better explain possible CPP triggering factors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…CPP patients have eight times more psychosomatic symptoms than controls 7 . The presence of family issues in most CPP patients suggests the importance of using psychotherapy to treat these females, as already emphasized by the literature 8,18 . Further qualitative studies may probably better explain possible CPP triggering factors.…”
Section: Discussionmentioning
confidence: 88%
“…There has been even further VAS decrease in patients submitted to cognitive-behavioral therapy being that this has only been applied to six cases, which has not provided statistical significance. It has to be stressed that patients were very resistant to accept psychotherapeutic aid, inasmuch that ¾ have not accepted it although being already a recommendation of the literature 1,2,8,18 . This is possibly a factor impairing ambulatory discharge of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions include Thomas et al18 and Weijenborg et al19 The fear-avoidance model of pain, commonly applied to musculoskeletal pain conditions, has also been found to be relevant to women with CPP 20. This study highlighted the importance of negative beliefs about the pain (“pain catastrophizing”).…”
Section: Introductionmentioning
confidence: 87%
“…There is also a growing body of research identifying subgroups of patients who exhibit high fear-avoidance behaviors in order to predict outcomes and match patient psychological characteristics with specific interventions. 112,113 Functionally, Sawamoto et al 114 found that negative expectation regarding a pain-producing stimulus increased brain activation in the ACC and IC compared to controls, and that negative expectation of a painful stimulus amplified perceived unpleasantness of an innocuous stimulus. Both Koyama et al 109 and Keltner et al 107 found that mPFC, ACC, and IC activations were directly related to expectation.…”
Section: Classical Conditioning and Expectationmentioning
confidence: 98%